Straightforward fabrication of bioactive polymeric surfaces for bacterial immobilization - Deveci, Gozde; Kocer, Sinem; Turgut-Balik, Dilek; Kahveci, Muhammet U. (TAYLOR & FRANCIS INC, 2025)
Rapid and reliable detection of pathogenic bacteria requires support materials relying on functional polymeric materials that can immobilize bacteria. Herein, a straightforward approach for the fabrication of surfaces for bacterial immobilization. The surfaces were designed to be conjugated with Concanavalin A (Con A), a lectin that recognizes mannosyl and glucosyl groups of lipopolysaccharides, the protective outer cell membrane of Gram-negative bacteria such as Escherichia coli. Two distinct surfaces, glass and polymeric microparticles, were chosen and modified for the Con A conjugation. Both surfaces were grafted with the same constituting monomers: poly(ethylene glycol) methyl ether methacrylate (PEGMA) and N-(methacryloxy)succinimide (NMAS) through a surface-initiated atom transfer radical polymerization. Subsequently, Con A was conjugated to the surfaces via succinimidyl functionalities of the P(PEGMA-co-NMAS)grafted to the surfaces. A green fluorescent protein (GFP)-expressing E. coli strain was utilized to monitor the bacterial attachment. Fluorescent microscopy results revealed that the Con A-conjugated surfaces captured GFP E. coli.
Keywords: Functional surface; Concanavalin A; bacterial immobilization; SI-ATRP; succinimide; TRANSFER RADICAL POLYMERIZATION; BLOCK-COPOLYMERS; COMBINATION; BIOSENSOR; AMINOLYSIS; ATRP; Polymer Science